The state of outsourcing in the Canadian mining industry. (December 2018) - Baatartogtokh, Baljir; Dunbar, W. Scott; van Zyl, Dirk
Abstract: Outsourcing, the practice of having company activities done by suppliers, has been practiced in the Canadian mining industry for some time. However, the extent of the practice is unknown. There are sound reasons for outsourcing rooted in some important economic concepts. Of interest is whether outsourcing is evolving to an "extreme" state where a mining company becomes the manager of a network of service and equipment suppliers. Such a state would have implications for innovation, for the manner in which mineral resources are developed, and for potential interactions between the industry and governments of developing countries that have large mineral resource endowments. A survey of 58 producing Canadian mining companies was conducted to determine which companies are outsourcing, how prevalent is outsourcing, what activities are being outsourced, why companies are outsourcing, what the risks of outsourcing are, and are mining and mineral processing core competencies of mining companies. The results are generally consistent with the economic concepts but questions concerning the risks of outsourcing and identification of core competencies of a mining company remain. It is clear that at present outsourcing is done in a strategic sense, likely dependent on particular situations. Highlights: Outsourcing is the deliberate decision not to internalize an activity. The practice of outsourcing has roots in well-established economic theories. More mining activities are outsourced than mineral processing and waste management activities. Access to specialized competencies is a strong reason for outsourcing. Access to innovation available from suppliers is not a strong reason for outsourcing. Reasons for outsourcing vary considerably. Core competencies of a mining company are difficult to define. Research is needed to determine how a mining company builds and maintains competitive advantage.